PENGARUH PRODUK DOMESTIK REGIONAL BRUTO(PDRB) DAN JUMLAH PENDUDUK TERHADAP SEKTOR PERTANIAN DI KABUPATEN BONE PADA TAHUN 2010-2020 - Anggadita, Nana Dwi; Haslindah, Haslindah (Faculty of Islamic Economics and Business, 2022)
Regional economic growth is measured by the development of Gross Regional Domestic Product (GRDP), which is basically the gross added value of goods and services generated from various economic activities. This study aims to describe the effect of Gross Regional Domestic Product (GRDP) and population on the agricultural sector in Bone Regency for the 2010-2020 period. The analysis method used is multiple linear regression, with the method of collecting documentation data. The type of data used in this study is secondary data obtained through the Official BPS website of Bone Regency. The results of this study show that 1) Gross Regional Domestic Product (GRDP) has no effect on the agricultural sector can be seen from the results of the t test which shows that the significant value produced is 0.059 >0.05 so that Ho's potesis is received. 2) The number of people has no effect on the agricultural sector can be seen from the results of the t test which proves that the significant value is high which is 0.146 > 0.05 so that Ho is accepted. 3) Gross Regional Domestic Product (GRDP) and population have a one-way effect on the agricultural sector can be seen from the results of the F test which proved a significant value of 0.49 and the F result of 3.838 < F table 3.41.